Influences of Coal Properties on the Principal Permeability Tensor during Primary Coalbed Methane Recovery: A Parametric Study. (14th August 2021) - Zang, Jie; Ma, Ze; Ge, Yong; Li, Chengxin
Abstract : Coal permeability is intrinsically anisotropic because of the cleat structure of coal. Therefore, coal permeability can be denoted by a second-order tensor under three-dimensional conditions. Our previous paper proposed an analytical model of the principal permeability tensor of coal during primary coalbed methane (CBM) recovery. Based on this model, 18 modeling cases were considered in the present study to evaluate how the principal permeabilities were influenced by representative coal properties (the areal porosity, the internal swelling ratio, and the Young modulus) during primary CBM recovery. The modeling results show that with regard to the influences of the areal porosity on the principal permeabilities, an increase in cleat porosity reduces the sensitivity of each principal permeability to pore pressure change. The magnitudes of the principal permeabilities are positively proportional to the internal swelling ratio. The principal permeabilities thus tend to monotonically increase with a depletion in the pore pressure when the internal swelling ratio increases. Because the internal swelling ratio represents the extent of gas-sorption-induced matrix deformation, an increase in the internal swelling ratio increases desorption-induced matrix shrinkage and thus induces an increase in permeability. The principal permeabilities are positively proportional to the isotropic principal Young moduli and the synchronously changing anisotropic principal Young moduli. On the other hand, the principal Young modulus within the plane of isotropy influences the principal permeabilities within this plane in diverse patterns depending on both the dip angle of the coalbed and the pitch angle of the cleat sets. The principal permeability perpendicular to the plane of isotropy is positively proportional to this principal Young modulus, and this correlation pattern is independent of both the dip angle and pitch angle.